Fluorescence Quantum Yields of Natural Organic Matter and Organic Compounds: Implications for the Fluorescence-based Interpretation of Organic Matter Composition - Wünsch, Urban J.; Murphy, Kathleen R.; Stedmon, Colin A. (Frontiers in Marine Science, 2015)
Absorbance and fluorescence spectroscopy are economical tools for tracing the supply, turnover and fate of dissolved organic matter (DOM). The colored and fluorescent fractions of DOM (CDOM and FDOM, respectively) are linked by the apparent fluorescence quantum yield (AQY) of DOM, which reflects the likelihood that chromophores emit fluorescence after absorbing light. Compared to the number of studies investigating CDOM and FDOM, few studies have systematically investigated AQY spectra for DOM, and linked them to fluorescence quantum yields (Ф) of organic compounds. To offer a standardized approach, a MATLAB toolbox for the determination of apparent quantum yields of DOM (aquaDOM), featuring two calculation approaches, was developed and used to derive AQYs for samples from the Norwegian Sea. Ф of the organic compounds varied between 0.00079 and 0.35, whereas the average AQY for DOM samples at 350 nm was 0.011 ± 0.003. The AQY at 350 nm increased with depth, while the AQY at 250 nm showed no trend. Laboratory tests indicated that Ф of compound mixtures are additive and represent an intermediate of the constituents. Additionally, the presence of non-fluorescent chromophores greatly suppressed calculated AQYs. Similar trends in the DOM AQY at 350 nm were observed in natural samples. We therefore hypothesize that fluorescence AQYs can indicate changes in the relative abundances of CDOM and FDOM. Additionally, the optical properties of 15 potential DOM constituents were determined and compared to more than 200 modelled spectra (PARAFAC components) in the OpenFluor database. Apparent matches, based on spectral similarity, were subsequently evaluated using molar fluorescence and absorbance. Five organic compounds were potential matches with PARAFAC components from 16 studies; however, the ability to confirm matches was limited due to multiple compounds exhibiting very similar spectra. This reiterates the fact that spectral similarity alone is insufficient evidence of the presence of particular compounds, and additional evidence is required.